2018
DOI: 10.3390/ijms19020604
|View full text |Cite
|
Sign up to set email alerts
|

The Connexin Mimetic Peptide Gap27 and Cx43-Knockdown Reveal Differential Roles for Connexin43 in Wound Closure Events in Skin Model Systems

Abstract: In the epidermis, remodelling of Connexin43 is a key event in wound closure. However, controversy between the role of connexin channel and non-channel functions exist. We compared the impact of SiRNA targeted to Connexin43 and the connexin mimetic peptide Gap27 on scrape wound closure rates and hemichannel signalling in adult keratinocytes (AK) and fibroblasts sourced from juvenile foreskin (JFF), human neonatal fibroblasts (HNDF) and adult dermal tissue (ADF). The impact of these agents, following 24 h exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 52 publications
2
48
2
Order By: Relevance
“…Gap27 blocks hemichannel and gap junctional communication without influence on Cx43 gene expression in keratinocytes [ 64 , 121 , 122 , 123 ]. It enhances keratinocyte migration rates, without altering cell proliferation supporting concepts that hemichannel activity is involved in keratinocyte galvanotaixis [ 61 , 124 ].…”
Section: Connexins As Therapeutic Targets In Epithelial Tissuesmentioning
confidence: 70%
See 1 more Smart Citation
“…Gap27 blocks hemichannel and gap junctional communication without influence on Cx43 gene expression in keratinocytes [ 64 , 121 , 122 , 123 ]. It enhances keratinocyte migration rates, without altering cell proliferation supporting concepts that hemichannel activity is involved in keratinocyte galvanotaixis [ 61 , 124 ].…”
Section: Connexins As Therapeutic Targets In Epithelial Tissuesmentioning
confidence: 70%
“…The localised switch in phosphorylation probably changes the functional signalling parameters of Cx43 channels, further enhancing migration of wound edge keratinocytes. This may include the induction of signalling pathways, including Transforming Growth Factor-β TGF-β and ECM deposition, all of which are key events in wound closure [ 61 , 62 , 63 ]. Upon re-stratification, levels of Cx43 are re-established [ 45 , 58 , 64 , 65 ].…”
Section: Connexins In the Epidermismentioning
confidence: 99%
“…Both have been widely used to inhibit CX mediated signalling events in diverse tissue networks (Willebrords, Maes, Crespo Yanguas, & Vinken, ). We have recently reported that Gap27 is effective in inhibiting ATP release from keratinocytes at concentrations of 100 nM, where it promotes keratinocyte migration with limited effect on proliferation (Faniku et al, ). Gap27 is reported to be specific for CX43 and CX37 by several groups (Martin, Wall, & Griffith, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Martin and co-workers have used an alternate gene knockdown approach, short interfering RNAs (siRNAs) targeted to Cx43, together with the Cx43 mimetic peptide Gap27, to study channel-dependent and independent effects of Cx43 in the response of dermal cells to injury [ 33 ]. Their data indicates that the response to targeting Cx43 varies between cell types (keratinocyte versus fibroblast) and between cells of the same type (skin fibroblasts), but of different tissue origins.…”
Section: Early Work On the Role Of Cx43 In Cutaneous Wound Healingmentioning
confidence: 99%